1375. Validation of a Syndromic Surveillance Query for Lyme Carditis – New York, 2017-2021. (15th December 2022) - Beeson, Amy; White, Jennifer; McCormick, David; Gates, Abigail; Hinckley, Alison F; Marx, Grace E
Abstract: Background: Lyme carditis is a rare and potentially fatal manifestation of Lyme disease. Although Lyme disease is nationally notifiable, data on specific clinical manifestations are not collected systematically. We sought to use a novel syndromic surveillance query to identify patients with Lyme carditis in New York State (excluding New York City) during 2017-2021. Methods: Using the National Syndromic Surveillance Program's BioSense Platform, we developed a query using a combination of diagnosis codes and chief complaint terms to identify emergency department visits related to Lyme carditis. We systematically reviewed and abstracted key information in each identified individual medical record through New York's regional health information exchange system, requesting supplemental records when needed. Two physicians independently assigned a clinical case status (confirmed; probable; not a case) to each abstracted record; when adjudications differed, an infectious disease physician provided a final adjudication. Positive predictive value for the query was calculated and characteristics of cases and non-cases were described. Results: The query identified 175 individuals. Records were available for review for 139 individuals. Among these, 37% (n = 52) were classified as confirmed, 17% (n = 24) as probable, and 45% (n = 63) as not a case. In total, we identified 76 cases of confirmed or probable Lyme carditis for which records were available; the positive predictive value of the query was 45%. Cases occurred in 28 of New York's 57 counties (excluding New York City); most (64%) occurred during May–September. Median age was 60 years for cases (IQR 33 – 73) and 67 years for non-cases (IQR 42 – 78) (p = 0.13); 29% of cases and 38% of non-cases were female (p = 0.23). Among cases, 76% had positive IgG or IgM immunoblots and 37% had second- or third-degree atrioventricular block. Conclusion: Using a syndromic surveillance query, we detected 76 cases of Lyme carditis, a rare disease of public health importance. Syndromic surveillance using this query may provide a useful marker for Lyme-endemic states to use to detect changing disease patterns, including temporal or spatial clusters of severe Lyme disease manifestations. Disclosures: All Authors : No reported disclosures.